ANALISIS PERBANDINGAN MOTIVASI BELAJAR SISWA DAN INTENSITAS GERAK PADA MODEL PEMBELAJARAN TAKTIS DAN TEKNIS PADA PERMAINAN INVASI - Stephani, Mesa Rahmi; Nur, Lutfi; Hambali, Burhan; Suherman, Adang; Subarjah, Herman (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
This study aims to look at differences in motivation and physical intensity in junior high school students through tactical and technical learning models in invasion games. This study used an experimental method with a post-test control group design. Sample selection using cluster random sampling was chosen to determine the experimental group and the control group. Each class consists of 24 students. From each class 8 students were taken (4 men; 4 women) because of the limited availability of the Polar Global Positioning System (GPS) instrument. Student motivation is measured using a questionnaire. Data is processed using independent sample t-test. The results showed that there were differences in the motivation and intensity of student movements in the tactical and technical learning model groups. The intensity and motivation of students in the tactical learning model group is higher than the technical learning model. The implications of this study can be used as empirical data related to motivation and intensity of movement influenced by tactical learning models in invasion games. So that the achievement of physical fitness can be obtained by taking into account the intensity of student movement during the Physical Education learning objectively.Â